A new HPLC-MS/MS method for the simultaneous determination of 36 polyphenols in blueberry, strawberry and their commercial products and determination of antioxidant activity. (15th January 2022) - Mustafa, Ahmed M.; Angeloni, Simone; Abouelenein, Doaa; Acquaticci, Laura; Xiao, Jianbo; Sagratini, Gianni; Maggi, Filippo; Vittori, Sauro; Caprioli, Giovanni
Highlights: A new HPLC-MS/MS method for analysis of 36 phenolics in berry fruits and jams. Blueberry exhibited higher contents of anthocyanins, flavonols and phenolic acids. Strawberry showed higher amounts of flavan-3-ols, dihydrochalcones and flavanones. Higher phenolic content in the blueberry justified greater antioxidant activity. This HPLC-MS/MS method is reliable for quality control analyses of fruit products. Abstract: Berry fruits consumption has increased in recent years because they are rich sources of polyphenols with reported health benefits. The aim of the present work was to develop a new comprehensive and fast HPLC-MS/MS method for simultaneous determination of 36 phenolic compounds (7 anthocyanins, 9 flavonols, 4 flavan-3-ols, 2 dihydrochalcones, 2 flavanones and 12 phenolic acids) present in blueberry, strawberry, and their fruit jam. Blueberry fruits showed higher contents of anthocyanins, flavonols and phenolic acids, while strawberry fruits exhibited higher contents of flavan-3-ols, dihydrochalcones and flavanones. Anthocyanins were the main phenolic constituents in both berries. Furthermore, the higher total phenolic content in the blueberry fruit and jam justified their greater antioxidant capacity measured by DPPH free radical assay, compared to strawberry. In conclusion, this new HPLC-MS/MS method is useful and reliable for quality control and authentication analyses of blueberry and strawberry fruits and their commercial food products, such as jams.